Multiprobe Microwave Multimeter Functional Design - Volkov, V. M.; Zaichenko, O. B. (Kontrast Publishing Enterprise, 2004)
Multiprobe microwave multimeter is a new type of measurement device representing an automatic multichannel system consisting of a very high frequency unit with passing power sensors and a computing unit on the basis of the microcontroller or PC and is intended for measurement incident, reflected and passing power, module and phase of a termination reflection coefficient, executing generator and termination checking in an" hot" mode. The methodology of the working MMM design with equidistant sensors arrangement.
Keywords: microwave devices; power measurement; microwave measurement; frequency measurement; phase measurement; microwave sensors; microcontrollers; reflection